Art, Code, and the Engine of Change. - Hertz, Paul (Art Journal)
The article discusses the effect of computers and digital technology on art, as seen primarily in the exhibition "Imaging by Numbers: A Historical View of the Computer Print," co-curated by the author at the Northwestern University art museum in 2008. Other topics discussed include: early forms of computer art, and succeeding terms such as "electronic art," "digital art," and "new media"; the development of computer science and its impact on artists; the use of algorithms in computer programming, graphics, and eventually art; and the idea of "virtual art."